TINJAUAN YURIDIS TERHADAP PERTANGGUNGJAWABAN PIDANA BAGI PELAKU TINDAK PIDANA KORUPSI DANA PEMULIHAN EKONOMI NASIONAL (PEN) - Gadman Futor Abdillah; Herdy Pratama (Fakultas Ilmu Sosial dan Humaniora, 2025)
The misuse of National Economic Recovery funds that occurred in Situbondo Regency is approaching one billion Rupiah. This fund is the General Allocation Fund in the Procurement of Consulting Services for the Preparation of Environmental Impact Analysis, which includes Environmental Balance Efforts and Environmental Management Efforts at the Environmental Service for the 2021 fiscal year. This study aims to determine the accountability for criminal acts of corruption of the 2021 Situbondo Regency National Economic Recovery funds and the prison sentences imposed are appropriate punishments for perpetrators of corruption. This type of legal research is descriptive normative legal research. Legal research is a process of finding legal rules, legal principles, and legal doctrines in order to answer legal issues faced in discussing problems. researchers will collect written data in the form of documents that become archives or copies. Library data is a secondary data source, so it can be a strengthening of research. The results of this study stated that when the work period ended, the procurement of consulting services for the preparation of Environmental Balance Efforts and Environmental Management Efforts at the Environmental Service was not completed on time. In this case, 4 suspects from the Environmental Service and 2 suspects from the private sector as service providers were involved. The consequences of the corruption committed by the defendant had social and moral impacts on state institutions and violated the principle of social justice. The defendant was sentenced to imprisonment, fines, compensation, revocation of functional positions and confiscation of assets.